Khư̄ khon ʻAndāman khư̄ khon raksā thalē (Khrư̄akhāi Khwāmrūammư̄ Fư̄nfū Chomchon Chāifang ʻAndāman, 2005)
Economic conditions in the Andaman Sea side of Southern Thailand after the Asia Tsunami in 2004.